PROFILE OF PHYSICAL FITNESS OF STUDENTS WHO DO FUTSAL (Fiep Bulletin - online, 2011)
The aim of this study was to evaluate the profile of physical fitness related to the performance of children aged 10 to 12 years, participants of the Sports Center Project UFRA in the city of Belém-PA. The sample comprised 62 boys, all participants of the project. For this analysis, were the following: body mass index (BMI), speed and flexibility. The tests were performed: 40 Seconds of Running, Jumping Horizontal, Test and Test of Flexibility mile. Evaluation of force was obtained from three horizontal jumps measured in metric scale (FERNANDES, 2005), the evaluation was carried out by the speed of 40 seconds Race (MATSUDO, 1983 apud FERNANDES (2005) and Body Mass Index (FERNANDES, 2005) to measure the flexibility of the protocol was used goniometry (DANTAS, 2001). The tests showed that the age of the children was a determinant for the outcome of the study, since the results showed that the average speed of children with 10 years was higher than the other, while in relation to flexibility, all tests showed that children of 12 years had greater resourcefulness, children of 11 years results in both tests of speed, flexibility and BMI, which include the band obtained by children of 10 and 12 years participating in the study.
Keywords: phisical apdation; children; futsal